2019
DOI: 10.4236/ojepi.2019.91004
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Practice of Proper Health Seeking Behaviour and Determinant of Self-Medication among Physicians and Nurses in a Tertiary Hospital in Southwest Nigeria

Abstract: Background: There is generally a lack of good health-seeking practices among health professionals due to a variety of factors, including the intensity of the medical practice itself. Doctors and nurses are perceived to have a good knowledge of ideal health-seeking behaviors and as such, it is important to determine the level of their awareness and estimate whether this knowledge is put into practice. This study, therefore, aimed to determine the level of awareness and practices of proper health-seeking behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 13 publications
3
19
0
Order By: Relevance
“…In this study, some nurses justified not following up on their health issues by being skeptical about observance of confidentiality in counseling and unwillingness to disclose their health status to colleagues. Similar findings were reported in previous studies 17,19,22,46. This problem is seen not only in nurses but also in other health care workers and to a greater extent in physicians.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, some nurses justified not following up on their health issues by being skeptical about observance of confidentiality in counseling and unwillingness to disclose their health status to colleagues. Similar findings were reported in previous studies 17,19,22,46. This problem is seen not only in nurses but also in other health care workers and to a greater extent in physicians.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, they are concerned about violation of their confidentiality by discussing their medical history with other colleagues and about their workplace's access to their information, which prevented them from seeking health care. 17,46 The results of this study showed that nurses had the benefits of quick access to medical services and constant presence of physicians, and if they were satisfied with the health care services provided at work, they could easily use them. However, the lack of access to health care services in the general population is always an important issue in HSB.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…35 36 The health-seeking behaviour of the HCWs in Nigeria and poor reporting of COVID-19 infection cases within this cohort is to be considered. There is evidence that the practice of self-medication and reluctance to obtain medical care is high among doctors and nurses in Nigeria [35][36][37][38][39] ; therein lies the possibility of nonreporting of mild cases. This behavourial pattern emphasises the need for more awareness and education on these issues within this group of healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, consideration must be given to the health-seeking behaviour of the healthcare workers in Nigeria and poor reporting of COVID-19 infection cases within this cohort. There is evidence that the practise of selfmedication and reluctancy to obtain medical care is high among doctors and nurses in Nigeria [19][20][21][22][23] . This behavourial pattern emphasises the need for more awareness and education on these issues within this group of healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%